2014
DOI: 10.1093/molbev/msu217
|View full text |Cite
|
Sign up to set email alerts
|

Functional Evolution of Cardiac MicroRNAs in Heart Development and Functions

Abstract: MicroRNAs (miRNAs) are a class of endogenous small noncoding RNAs that regulate gene expression either by degrading target mRNAs or by suppressing protein translation. miRNAs have been found to be involved in many biological processes, such as development, differentiation, and growth. However, the evolution of miRNA regulatory functions and networks has not been well studied. In this study, we conducted a cross-species analysis to study the evolution of cardiac miRNAs and their regulatory functions and network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…In the same context, the roles of epigenetic changes and miRNAs have only recently started to be addressed. 174 The success in generating cardiac mesoderm progeny calls for systematic experimental designs focusing on the controlled specification to distinct heart cell types such as ventricular cardiomyocytes, and the impartation with high fidelity of attributes of corresponding native cell populations. Given the rapid progress thus far in the development of efficient strategies for the production of heart cells, we anticipate the realization of more hPSC-derived cardiac cell applications envisioned in regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%
“…In the same context, the roles of epigenetic changes and miRNAs have only recently started to be addressed. 174 The success in generating cardiac mesoderm progeny calls for systematic experimental designs focusing on the controlled specification to distinct heart cell types such as ventricular cardiomyocytes, and the impartation with high fidelity of attributes of corresponding native cell populations. Given the rapid progress thus far in the development of efficient strategies for the production of heart cells, we anticipate the realization of more hPSC-derived cardiac cell applications envisioned in regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are highly conserved during evolution with a well-established role in cell proliferation, differentiation, metabolism, apoptosis, development, and aging as well as in the pathophysiology of many diseases such as cancer, CVDs, and neurological disorders (11). The miRNA coding regions are mainly present in the genome as clusters (12).…”
Section: Micrornasmentioning
confidence: 99%
“…Net gain of miRNAs was estimated as 0.3-1 new gene per Myr 56 57 . Several studies showed that the evolution of miRNAs and their regulatory networks were adaptive to various developmental processes, such as reproduction and metamorphosis in Drosophila , and the cardiac and muscle development in vertebrates 40 58 59 60 61 . In addition, the X-linked miRNAs evolved rapidly in mammals, implying possible roles in male reproduction 62 63 .…”
mentioning
confidence: 99%